140 Fibrocalcific volume in aortic valve stenosis using contrast-enhanced computed tomography. (6th June 2022) - Joshi, Shruti; Lembo, Maria; Bing, Rong; Carnevale, Lorenzo; Tzolos, Evangelos; Pawade, Tania A; Doris, Mhairi K; Dey, Damini; Newby, David E; Dweck, Marc R
Abstract : Introduction: Computed tomography (CT) calcium score is a widely used clinically validated approach used for assessment of aortic stenosis (AS) severity however it does not account for the fibrotic valve thickening seen in AS. We sought to develop a robust contrast-enhanced computed tomography (CT) method for evaluating the anatomic burden of fibro-calcific thickening in patients with AS. We then investigated its reproducibility and associations with both haemodynamic AS severity and progression. Methods: In a post-hoc analysis of 136 patients with calcific AS enrolled in the SALTIRE II trial (NCT-02132026), fibrocalcific volume was calculated using a gaussian mixture model applied to contrast-enhanced CT at baseline and at 1-year follow up (Autoplaque software, Cedars-Sinai Medical Center). Three compartments (blood pool, non-calcific and calcific tissue) were defined by the distribution of attenuation (Hounsfield Units) within the aortic valve volume of interest, automatically generating thresholds for non-calcific and calcific tissue (Figure 1). Fibrocalcific volume was indexed for CT annulus area, compared with echocardiographic parameters of AS severity and progression, and scan-rescan reproducibility assessed. Cohen's d-statistic (d) was calculated to express the magnitude of progression normalized by the uncertainty in the measurement technique (calculated by dividing the annualised progression by measurement repeatability, defined as (1/√2) of the standard deviation of the differences between measurements at scan and rescan within the reproducibility cohort). Results: Participants were median age of 72 (IQR: 68–76) years, majority were male (79%) and all had a left ventricular ejection fraction of >50%. Fibrocalcific volume analysis was completed in 5.8±1.0 minute/scan and demonstrated excellent scan-rescan reproducibility (mean difference -1%, limits of agreement -9% to 7%). Fibrocalcific volume correlated strongly with peak aortic jet velocity (rho=0.70, p<0.0001), with stronger associations than those observed for the calcific volume (CV) or non-calcific volume (NCV) alone (rho=0.61 and rho=0.30 respectively, both p<0.0001) or the Agatston calcium score (rho=0.63, p<0.0001), Table 1. Baseline fibrocalcific volume was also the strongest predictor of subsequent AS progression in terms of change in aortic valve peak velocity (rho=0.29, p=0.006) and mean gradient (rho=0.39, p<0.0001), Table 2. Furthermore, progression-to-noise ratio for fibrocalcific volume was favourable (Cohen's d=0.62), indicating that group sizes of 21, 46 and 170 participants would be required to demonstrate a 30%, 20% and 10% reductions in fibrocalcific volume with a novel drug therapy (α=0.05, power=80%) Conclusion: Indexed fibrocalcific volume can provide a rapid and robust assessment of fibrocalcific thickening in patients with AS. Fibrocalcific volume correlates well with disease severity, predicts progression and holds promise in tracking disease progression and therapeutic response. Conflict of Interest: None